(untitled) (Clinics, 2021)
OBJECTIVES: This study explored the effects of the timing of laparoscopic cholecystectomy (LC) after endoscopic retrograde cholangiopancreatography (ERCP) on liver function, bile biochemical indices, inflammatory reactions, and cholecysto-choledocholithiasis patient prognoses. METHODS: A total of 103 cholecysto-choledocholithiasis patients were stratified into control (CG; n=51; LC at 4–7 d after ERCP) and observation groups (OG; n=52; LC at 1–3 d after ERCP) using a random number table. RESULTS: The surgical time was shorter and intraoperative blood loss was less in OG than in CG, and the two groups were not statistically different in terms of time to the first passage of gas through anus, length of postoperative hospital stay, conversion rate to laparotomy, and stone-free rate. Four weeks after LC, alanine aminotransferase (ALT), total bilirubin (TBil), albumin (ALB), and glutamyl transpeptidase (GGT) levels declined in both groups, but the difference was not statistically significant. Three days after LC, total bile acid (TBA) levels increased, and cholesterol (CHO), unconjugated bilirubin (UCB), and TBiL levels were reduced in both groups, but were not statistically different (p40.05). Three days after LC, interleukin (IL)-6, procalcitonin (PCT), and high-sensitivity C-reactive protein (hs-CRP) levels in the serum and bile increased in both groups and were lower in OG. The total incidence of perioperative complications was 1.92% in OG, which was lower than 15.69% in the CG. CONCLUSION: For cholecysto-choledocholithiasis patients, LC at 1–3 d after ERCP can shorten surgical times, reduce intraoperative blood loss, improve liver function and bile biochemistry, relieve inflammatory reactions, reduce complications, and improve prognoses.